How nutrition-sensitive agriculture programs can realize both nutrition and gender equality goals - Malapit, Hazel J. (CGIAR GENDER Impact Platform, 2021)
Globally, malnutrition remains unacceptably high, and hard-won progress is further threatened by the impacts of the COVID-19 pandemic. Agriculture, with its critical role in the production, availability and consumption of food, as well as rural livelihoods and incomes, must step up to help address nutrition challenges. Nutrition-sensitive agriculture programs (NSAPs) are one way that agriculture can contribute to achieving our global nutrition goals. These programs also have the potential to help meet other critical development objectives, specifically women’s empowerment and shifting of underlying barriers that perpetuate gender inequalities.